Report proposed new design scheme of boutique cafe for SEED (Padini Holdings Berhad) at Millennium Square, Dataran Millennium PJ, No 98 Jalan 14/1, 46100 Petaling Jaya Selangor / Nur Shahirah Kaulan - Kaulan, Nur Shahirah (Faculty of Architecture, Planning and Surveying, 2009)
The competitive environment in the retail and Food and Beverage industry is expected to get more intense and crowded. More foreign brand names have now set up shop in Malaysia and more are still to come. Business conditions in this sector will become less forgiving; complacency and a slowness to act or change will be severely punished. To succeed in such an environment, retailers and brand owners alike will have to rethink their existing work practices and business strategies to see if more efficiencies and competitive advantage can be secured by doing things differently. Best practices in product design and merchandising, customer service, data collection and analysis, store layouts, inventory control, etc., will have to be reviewed, modified and adopted just so a retailer can stay relevant and profitable. This proposal is for open second branch SEED boutique and cafe at Millennium Square Petaling Jaya, Selangor. The main objective is to proposed new concept and design for SEED boutique and cafe. Enhance to make a perfect boutique cafe in good environment and services. Wireless internet service will be providing in this second branch of SEED boutique and cafe. Observation and compilation data was done before the design process. A good proposal must have a good research to make this proposal successful. The information of client must be research before to proceed this project proposal and also site proposed information. Finally, analysis all the data will be a guider in design process. The proposed design concept is “The Paradox Boolean” to follow the client image and identity.